Determinants of corporate cash holding: An Empirical investigation of UK companies - Du, Xinpei (2013)
This dissertation examines the determinants of corporate cash holdings by publicly traded UK firms over the period 1998 to 2012. The empirical evidence suggests that firm with greater investment opportunities, more cash flow and a higher level of cash flow uncertainty hold relatively higher level of cash. It also finds that firm size, capital expenditure, net working capital and dividend payment are negatively related to corporate cash holdings. Moreover, the effect of leverage on cash holding is ambiguity. In addition, the special attention is paid to the crisis years. The results show that cash ratio increases and leverage and R&D expenditure become more important during the global financial crisis.